Investigating barriers to "using information" in electronic resources: A study with e‐book users. Issue 1 (24th October 2017) - Potnis, Devendra; Deosthali, Kanchan; Pino, Janine
ABSTRACT: Students' ability to use information plays a key role in influencing their adoption and continued usage of e‐books. This pilot study investigates the barriers to using (i.e., searching, managing, processing and applying) information in e‐books experienced by 25 library and information science graduate students (LISGS) at a land‐grant university in the United States. The analysis of study participants' in‐depth qualitative responses using grounded theory principles reveals 60 barriers that affect their ability to use information. These barriers are related to (a) e‐readers, (b) features of e‐books, (c) psychological, somatic, and cognitive status of the respondents, (d) cost and (e) policies. We present the adverse effects of these barriers on the respondents' ability to search, manage, process and apply information in e‐books. For instance, the psychological, somatic and cognitive statuses of respondents affect their ability to process information the most. Barriers related to e‐readers and e‐books have collectively the most damaging effect on the respondent's ability to search, manage, process and apply information. Due to a series of unavoidable barriers, respondents who originally intend to use e‐books for utilitarian purposes end up using this electronic resource mostly for hedonistic reasons. Implications are discussed at the end.